Post Covid-19 : Impacts on Economy - Rozina, Muzammil (2021)
The world has become a worldwide town. The nations are coming nearer to one another, voyaging is getting more secure and simpler. Countries are meeting up through exchange, business and the travel industry. Quite possibly the main thing which was dismissed in this quick period was the transmission of infections from one country to another. As the movement becomes more secure and quicker the transmission of sicknesses turns out to be quicker